Concepts of the rectovaginal septum: implications for function and surgery. Issue 6 (June 2016) - Dariane, Charles; Moszkowicz, David; Peschaud, Frédérique
Abstract Introduction In the pelvis, the rectogenital septum (RGS) separates the urogenital compartment from the digestive compartment. In men, it corresponds to Denonvilliers' rectoprostatic fascia or rectovesical septum (RVS). Its purpose—and, indeed, its existence—are controversial in women. The purpose of this review was to update knowledge about the RGS in women and, in particular, to clarify its relationship to pelvic nerves in order to deduce practical consequences of pelvic surgery and compare it to the RVS in men. Methods A review of the anatomical and surgical literature was undertaken. Evidence for embryological origin, composition, and surgical importance of the RGS in women and men is suggested. Results This manuscript presents evidence of the existence of the RGS in both women (rectovaginal septum, RVaS) and men (rectovesical septum, RVS). It originates from the genital structures and extends from the rectogenital pouch to the perineal body. It is composed of connective tissue associated with bundles of smooth muscle cells and has lateral expansions in close contact with neurovascular bundles originating from the inferior hypogastric plexus. During pelvic surgery for carcinoma, preservation of nerve fibers of erectile bodies is necessary if possible. The RGS is thus an important surgical landmark during urogenital sinus surgery, prolapse surgery, and proctectomy in women as well as during proctectomy and prostatectomy in men. Conclusions The RGS is present in women as well as in men, with great similarities between the two sexes. It represents an important surgical landmark during pelvic nerve-sparing surgery.